Relevansi Ajaran Catur Varna Terhadap Struktur Sosial Masyarakat Hindu Kontemporer - Rahayu Widyani, Ni Made (Satya Widya: Jurnal Studi Agama, 2025)
Abstract The doctrine of Catur Varna is a key concept in Hinduism that structures social roles based on inner qualities, work tendencies, and spiritual–ethical values. Consisting of Brahmana, Ksatriya, Vaisya, and Sudra, each Varna carries specific responsibilities aimed at sustaining social harmony. In modern contexts shaped by globalization, industrialization, and evolving religious practices, the interpretation of Catur Varna has shifted significantly. This article examines its contemporary relevance by analyzing socio-cultural changes, transformations in social structure, and the rise of more egalitarian theological interpretations. Using a qualitative literature review, the study draws on Hindu scriptures—such as the Vedas, Bhagavadgita, and Smrti—along with sociological theories and empirical research on Hindu communities in India, Bali, and the diaspora. The findings reveal that Catur Varna remains relevant when viewed as an ethical and professional framework based on guna and karma (aptitude and action), rather than as a hierarchical system that fosters discrimination. In Bali, Varna is increasingly interpreted as part of dharmic values guiding individuals to fulfill their swadharma according to competence and vocation. Globally, it functions as a universal ethical principle applicable to leadership, organizational governance, character education, and professional ethics. The study concludes that Catur Varna, when reinterpreted through the Bhagavadgita’s emphasis on spiritual equality, serves as a philosophical foundation for a just and harmonious modern society. Keywords: Catur Varna, swadharma, social structure, guna-karma, modern Hindu society.